Long-term follow up to determine the prognostic value of imaging after urinary tract infections. Part 2: Scarring. Issue 5 (May 1995) - Merrick, M V; Notghi, A; Chalmers, N; Wilkinson, A G; Uttley, W S
Abstract : Long term follow up of children with urinary tract infections, in whom imaging investigations were performed at presentation, has been used to identify features that distinguish those at greatest risk of progressive renal damage. No single investigation at presentation was able to predict subsequent deterioration but, by employing a combination of imaging investigations, it was possible to separate groups with high or low probability of progressive damage. In the low risk group the incidence of progressive damage was 0.2% (95% confidence interval (CI) 0 to 1.3%). The combination of both scarring and reflux at presentation, or one only of these but accompanied by subsequent documented urinary tract infection, was associated with a 17-fold (95% CI 2.5 to 118) increase in the relative risk of progressive renal damage compared with children without these features. The recommended combination of investigations at presentation for girls of any age and boys over 1 year is ultrasound and dimercaptosuccinic acid (DMSA) scintigraphy in all, to detect both scarring and significant structural abnormalities, renography in children with dilatation of any part of the urinary tract on ultrasound, to distinguish dilatation from obstruction, and an isotope voiding study in all who have acquired bladder control. This gives the best separation between those at high and those at low risk of progressive damage with least radiation dose and lowest rate of instrumentation. Micturating cystourethrography (MCU) should be restricted to girls who have not acquired bladder control, unless there is reason to suspect a significant structural abnormality such as urethral valves. A single non-febrile urinary tract infection that responds promptly to treatment is not a justification for performing MCU in boys under 1 year or in children of any age with bladder control. No case can be made for any abbreviated schedule of investigation. These risk factors should be taken into account when designing follow up protocols.